Long-Term, Patient-Level Analysis of Radiofrequency Renal Denervation in the SYMPLICITY Clinical Trial Program - Mahfoud, Felix; Townsend, Raymond R.; Kandzari, David E.; Mancia, Giuseppe; Whitbourn, Robert; Lauder, Lucas; Bhatt, Deepak L.; Kario, Kazuomi; Schmieder, Roland; Schlaich, Markus; Fahy, Martin; Böhm, Michael (JACC: Advances, 2025)
Background: Renal denervation (RDN) lowers blood pressure (BP) in patients with uncontrolled hypertension. Current guidelines recommend RDN for patients with uncontrolled BP despite the use of antihypertensive (AH) medications. Durability of BP reductions and assessment of which patient baseline characteristics correlate with subsequent BP reductions are scarce. Objectives: The authors leveraged patient data from the entire SYMPLICITY Clinical program to model long-term BP reductions and assess patient characteristics associated with future BP reductions. Methods: Repeated BP measurements from each patient were analyzed using linear mixed models. Models were fitted with office systolic BP (SBP), 24-h ambulatory SBP, office diastolic BP (DBP), and 24-h ambulatory DBP as outcome variables. Baseline BP, baseline number of AH medications, AH medications over time, and other variables were included as fixed effects. Results: The mixed model included data from 4,155 patients treated with the Symplicity RDN system. The mean age was 60 ± 12 years, 40.4% of whom were female. Estimated, longitudinal office and 24-h ambulatory SBP changes through 36 months, after adjusting for AH medication effects, were biphasic, with a steep reduction after RDN through the first 6 months followed by continuous and steady reductions in office and 24-h SBP and DBP afterward through 36 months. Higher baseline office systolic or 24-h ambulatory SBP were correlated with greater reductions through follow-up in office and 24-h SBP, respectively. Patient characteristics consistent with high sympathetic nerve activity, such as atrial fibrillation and type 2 diabetes, emerged as statistically significant covariates associated with greater office systolic and office and 24-h diastolic BP reductions, respectively. Conclusions: Modeling suggested patients have durable BP reductions following RDN, with a steep immediate reduction followed by a steady reduction through 3 years.
CRIS-Team Scopus Importer:2025-02-28
Keywords: hypertension; linear regression model; renal denervation